Self-Healing of Concrete Cracks by Ceramsite-Loaded Microorganisms - Jing Xu; Xianzhi Wang; Junqing Zuo; Xiaoyan Liu (Advances in Materials Science and Engineering)
Protective carrier is essential for the self-healing of concrete cracks by microbially induced CaCO3 precipitation, owing to the harsh conditions in concrete. In this paper, porous ceramsite particles are used as microbial carrier. Heat treatment and NaOH soaking are first employed to improve the loading content of the ceramsite. The viability of bacterial spores is assessed by urea decomposition measurements. Then, the self-healing efficiency of concrete cracks by spores is evaluated by a series of tests including compressive strength regain, water uptake, and visual inspection of cracks. Results indicate that heat treatment can improve the loading content of ceramsite while not leading to a reduction of concrete strength by the ceramsite addition. The optimal heating temperature is 750°C. Ceramsite particles act as a shelter and protect spores from high-pH environment in concrete. When nutrients and spores are incorporated in ceramsite particles at the same time, nutrients are well accessible to the cells. The regain ratio of the compressive strength increases over 20%, and the water absorption ratio decreases about 30% compared with the control. The healing ratio of cracks reaches 86%, and the maximum crack width healed is near 0.3 mm.